1983
DOI: 10.1159/000183054
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Intrarenal Cross-Linked Fibrin in Children with Various Renal Diseases

Abstract: The localization of intrarenal cross-linked fibrin was examined by the effect of monochloroacetic acid treatment on the kidney sections. In acute glomerulonephritis or in mild diffuse or focal proliferative type of nephritis, cross-linked fibrin was observed mainly within glomerular capillary walls. Extension of cross-linked fibrin deposit over the mesangium or sclerotic area was seen in moderate to severe proliferative type of nephritis or in membranoproliferative glomerulonephritis. In hemolytic uremic syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Yoshioka et al [20] reported that the F XIII activity decreased in children with acute poststreptococcal glomerulonephritis, HSP nephritis and rapidly progressive glomerulonephritis. Kamitsuji et al [21] showed the deposition of F XIII in the glomeruli of children with various renal diseases including HSP nephritis. Decreased F XIII activity may thus result from the enhanced fibrin formation in the kidney [20].…”
Section: Discussionmentioning
confidence: 99%
“…Yoshioka et al [20] reported that the F XIII activity decreased in children with acute poststreptococcal glomerulonephritis, HSP nephritis and rapidly progressive glomerulonephritis. Kamitsuji et al [21] showed the deposition of F XIII in the glomeruli of children with various renal diseases including HSP nephritis. Decreased F XIII activity may thus result from the enhanced fibrin formation in the kidney [20].…”
Section: Discussionmentioning
confidence: 99%
“…And substances released from platelets can be related to polymorphonuclear neutrophil migration, mesangial cell proliferation, complement activation, and increased permeability of the glomerular basement mem brane [10,20], Intraglomerular deposition of platelets, FRA and var ious coagulation factors has been identified in renal diseases [16][17][18]. Recent reports have described the intraglomerular deposition of FRA, F-XIIIa and F-XIlIs in GN and described the deposition of FRA, FDP-D and FDP-E in the glomeruli in GN [21][22][23]. In addition, Takemura et al [24] have shown the glomerular deposition of crosslinked Fibrin in renal diseases by using a mono clonal antibody that reacts with XL-FDP.…”
Section: Discussionmentioning
confidence: 99%